Retraction: A005, a novel inhibitor of phosphatidylinositol 3-kinase/mammalian target of rapamycin, prevents osteosarcoma-induced osteolysis. (4th April 2018) - Lian, Zhen; Han, Jinsong; Huang, Lin; Wei, Chengming; Fan, Yongyong; Xu, Jiake; Zhou, Mengyu; Feng, Haotian; Liu, Qian; Chen, Lingzi; Li, Zhaoning; Cheng, Haichun; et al.
Abstract: Osteosarcoma is the most frequent primary bone tumor in children and adolescents. The phosphatidylinositol 3-kinase (PI3K)/mammalian target of rapamycin (mTOR) signaling pathway is an attractive anticancer target because it plays key roles in the regulation of cell growth, division and differentiation. In this study, we demonstrated high expression of PI3K/mTOR signaling pathway-related genes in patients with osteosarcoma. We thus investigated the effects of A005, a newly synthesized dual PI3K/mTOR inhibitor, on osteosarcoma cells and in a mouse xenograft tumor model. The results confirmed that A005 inhibited the proliferation, migration and invasion of human osteosarcoma cells. In addition, A005 also inhibited receptor activator of nuclear factor kappa-B ligand (RANKL)-induced osteoclast differentiation and bone resorption in vitro . Therefore, A005 was further applied to a SaOS-2 osteosarcoma-induced mouse osteolysis model. A005 inhibited tumor growth and prevented osteosarcoma-associated osteolysis via modulation of the PI3K/AKT/mTOR pathway. Overall, our results showed that A005 inhibited osteoclastogenesis and prevented osteosarcoma-induced bone osteolysis by suppressing PI3K/AKT/mTOR signaling. These findings indicated that A005 may be a promising candidate drug for the treatment of human osteosarcoma.